Revolusi Digital : Pemanfaatan Teknologi AI Dalam Display Produk UMKM Olahan Hasil Laut - Nalendra, Muhammad Adi Sukma; Caniago, Deosa Putra; Hernando, Luki; Husna, Assaidatul; Sapitri, Ria; Kremer, Hendri; Harahap, Widiya Lestari; Nurcholiq, Rini (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2023)
The application of AI technology that is currently developing is very helpful in supporting the progress of MSMEs in various fields. By utilizing AI technology, it can help MSMEs who are having problems with product design and online marketing. This PkM aims to support the development of marine processed MSMEs in the Islands. The Pkm forum will provide knowledge and skills to MSMEs members for producing attractive and effective visual content and utilizing AI technology in marketing strategies. In this community service, the methods used are socialization by delivering equipment, practising using AI technology and discussions. In this way, it is hoped that MSMEs can increase its competitiveness and market share for processed seafood products, as well as support the Batam City government program in developing the MSMEs sector. Through this service, it is hoped that marine processed MSMEs in the Riau Islands can optimize their business potential by utilizing AI technology and visual communication in marketing. This activity will provide knowledge about the quality of promotional messages and attractive visual product presentations, so that MSMEs can produce marketing content that is effective in attracting attention and influencing the target audience. By increasing knowledge and skills in digital marketing, it is hoped that MSMEs can compete globally in developing the MSMEs sector and increasing exports of processed seafood products in the Riau Islands region, especially in Batam City.Keywords: AI; UMKM; Marketing Abstrak: Penerapan teknologi AI yang berkembang saat ini sangat membantu dalam mendukung kemajuan UMKM diberbagai bidang. Dengan memanfaatkan Teknologi AI dapat membantu UMKM yang terkendala dengan desain produk dan pemasaran secara online. PkM ini bertujuan untuk mendukung pengembangan UMKM olahan laut di Kepulauan. Dalam Pkm yang diselenggarakan akan memberikan pengetahuan dan keterampilan kepada anggota UMKM dalam menghasilkan konten visual yang menarik dan efektif serta memanfaatkan teknologi AI dalam strategi pemasaran. Dalam Pengabdian masyarakat ini metode yang digunakan yaitu sosialisasi dengan penyampaian materi, praktek menggunakan teknologi AI dan diskusi. Dengan demikian, diharapkan UMKM dapat meningkatkan daya saing dan pangsa pasar produk olahan laut, serta mendukung program pemerintah Kota Batam dalam mengembangkan sektor UMKM. Melalui pengabdian ini, diharapkan UMKM olahan laut di Kepulauan Riau dapat mengoptimalkan potensi bisnis mereka dengan memanfaatkan teknologi AI dan komunikasi visual dalam pemasaran. Kegiatan ini akan memberikan pembekalan pengetahuan tentang kualitas pesan promosi dan penyajian produk visual yang menarik, sehingga UMKM dapat menghasilkan konten pemasaran yang efektif dalam menarik perhatian dan mempengaruhi target audiens. Dengan peningkatan pengetahuan dan keterampilan dalam pemasaran digital, diharapkan UMKM dapat bersaing secara global dalam mengembangkan sektor UMKM serta meningkatkan ekspor produk olahan laut di wilayah Kepulauan Riau, khususnya di Kota Batam.Kata kunci: AI; UMKM; Pemasaran